Dynamic Analysis on the Safety Criteria of the Conceptual Core Design in MTR-type Research Reactor - T. Surbakti; S. Pinem; L. Suparlina (PPIKSN-BATAN, 2018)
One of thehigh-priority research activities in BATAN is designing a new MTR-type research reactor with a new fuel. The core follows a compact core model that consists of 16 fuels and 4 control rods. The increasing heat flux at the fuel will cause the temperature of the fuel and cladding to increase so that the coolant flow rate needs tobe increased. However, the coolant flow rate in the fuel element is limited by the thermal-hydraulic stability in the core. Therefore, dynamic analysis is important in evaluating the design and operation of nuclear reactor safety. The objective of this research work is to carry out a dynamic analysis for a conceptual MTR research reactor core fuelled with the low-enrichment U9Mo-Al dispersion. The calculations were performed using WIMSD-5B, Batan-2DIFF, Batan-3DIFF, POKDYN, and MTRDYN codes. Steady-state thermal-hydraulic parameters and dynamic analysis were determined using the MTRDYN code. The calculation results show that the maximum temperatures of the coolant, cladding, and fuel meat with the uranium density of 3.96 g cm-3 are 76.01 °C, 192.02 °C, and 196.24 °C, respectively. The maximum value of fuel meat temperature for safety limit is 210 °C, which means that the maximum temperatures fulfill the design limit, and therefore the reactor operates safely at the nominal power. The dynamic analysis shows that inherent safety can protect the reactor operation when insertion of reactivity occurs in the core.